Impact of Adding Urethral Sonography with Retrograde Urethrography in Preoperative Assessment of Anterior Urethral Stricture - Nidhi Sehgal; Vinod Priyadarshi (Journal of Medical Ultrasound)
Background: Even with underlying risk factors and limitations, retrograde urethrography (RGU) is the most popular imaging modality in the assessment of anterior urethral stricture. Urethral sonography (SUG) is an able imaging modality in use for the last few years which evaluates anterior urethral stricture without these risks, though it is still not much popular due to its complexity. This prospective study was designed to compare the assessment made on SUG with the results of RGU and to analyze its impact on surgical decision-making when the results of SUG were taken into consideration with RGU. Methods: Thirty patients with anterior urethral stricture were assessed for stricture location, length, and associated urethral pathologies with RGU and surgery planned accordingly. Later, all were reevaluated with SUG, results compared with that of RGU and surgery replanned, considering both RGU and SUG findings. All results were compared with operative findings. Results: The mean stricture lengths on SUG, RGU, and surgery were 20.45 mm, 17.15 mm, and 20.38 mm, respectively. Overall sensitivity and specificity of SUG in actual stricture length prediction were 92.3% and 96.1%, whereas these were 78.9% and 85.1%, respectively, on RGU. Spongiofibrosis was assessed only with SUG, that too, with 85%–90% accuracy. Surgical plan was changed in 31% of cases when SUG findings were taken into account along with RGU findings. Conclusion: SUG was found more precise modality in the measurement of stricture length and more informative and elaborative in providing added knowledge of degree of spongiofibrosis and associated pathologies of diseased urethra and periurethral tissue. For better preoperative planning of anterior urethral strictures, SUG should be added to work-up along with RGU.